TRIPS Agreement, International Technology Transfer and Least Developed Countries - Mark V. Shugurov (Centre for Behaviour and Wellness Advocacy, 2015)
The author examines the role of the trade-related aspects of intellectual property rights (TRIPS Agreement) in facilitation the international technology transfer to least developed countries (LDCs). The primary purpose of this study is to investigate the new conditions of technology development of LDCs connected with TRIPS adoption. Special attention is paid to the potentials of Article 66.2 for solving the problem of LDCs capacity building. The article presents detailed analysis of the discussions on the impact of the TRIPS provisions concerning the strengthening of the intellectual property rights (IPRs) and the protection of technology transfer to LDCs. An important finding of this study is the recognition of the need to take urgent measures for the transition unto a new model of partnership between developed countries and LDCs in area of technology transfer and IPRs protection. The study concluded that a new model needed to be elaborated at the international level should be based on the effective implementation of Article 66.2 of the TRIPS Agreement.